2012
DOI: 10.1111/tbj.12042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tumor Histology on Preoperative Staging Accuracy of Breast Metastases to the Axilla

Abstract: Histologic confirmation of axillary nodal metastases preoperatively avoids a sentinel node biopsy and enables a one step surgical procedure. The aim of this study was to establish the local positive predictive value of axillary ultrasound (AUS) and guided needle core biopsy (NCB) in axillary staging of breast cancer, and to identify factors influencing yield. A prospective audit of 142 consecutive patients (screening and symptomatic) presenting from 1st December 2008-31st May 2009 with breast lesions categoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…In previous single‐centre studies there has been speculation regarding the difference in AUS sensitivity based on tumour subtype. However, all of these studies included significantly lower numbers of patients compared with the present study. The majority of comparative studies, however, showed no difference in AUS sensitivity based on tumour subtype.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In previous single‐centre studies there has been speculation regarding the difference in AUS sensitivity based on tumour subtype. However, all of these studies included significantly lower numbers of patients compared with the present study. The majority of comparative studies, however, showed no difference in AUS sensitivity based on tumour subtype.…”
Section: Discussionmentioning
confidence: 58%
“…Johnson and colleagues found, however, that in primary lobular carcinoma AUS may be less accurate and a negative result is more likely to be spurious than with primary ductal carcinoma. Hackney and co‐workers demonstrated that the most significant factor in producing discordance between preoperative AUS and definitive histological evidence of lymph node metastasis was the lobular subtype. In addition, Jackson et al .…”
Section: Introductionmentioning
confidence: 99%
“…Some nomograms described in the published reports include the pathology subtype as a significant factor predicting NSLN involvement but other reviews have not found this feature significant . Sensitivity of axillary ultrasound has been reported to be much lower in ILC compared to other pathology subtypes (36% vs 76%) . This difference in axillary ultrasound sensibility could be an explanation for our finding: despite performing axillary ultrasound to all our patients previously to surgery, SLN biopsy would have been performed in a high proportion of ILC with a significant axillary neoplastic load as a result of ultrasound inability to detect axillary infiltration in these cases.…”
Section: Discussionmentioning
confidence: 69%
“…Deficiency in imaging of axillary adenopathy is experienced when evaluating invasive nonductal carcinoma histologic subtypes, such as ILC and invasive mammary carcinoma . Furthermore, limitations in spatial resolution of imaging modalities compromise detection of metastatic deposits too small to characterize on imaging, in our study defined as micrometastases.…”
Section: Discussionmentioning
confidence: 94%